Association of Traumatic Brain Injury With Vestibular Dysfunction and Dizziness in Post-9/11 Veterans. Issue 3 (May 2020) - Swan, Alicia A.; Nelson, Jeremy T.; Pogoda, Terri K.; Akin, Faith W.; Riska, Kristal M.; Hall, Courtney D.; Amuan, Megan E.; Yaffe, Kristine; Pugh, Mary Jo
Abstract : Objective: To describe the prevalence and impact of vestibular dysfunction and nonspecific dizziness diagnoses and explore their associations with traumatic brain injury (TBI) severity, mechanism, and postconcussive comorbidities among post-9/11 veterans. Setting: Administrative medical record data from the US Departments of Defense and Veterans Affairs (VA). Participants: Post-9/11 veterans with at least 3 years of VA care. Design: Cross-sectional, retrospective, observational study. Main Measures: International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes for TBI, vestibular dysfunction, dizziness, and other commonly associated postconcussive conditions; Neurobehavioral Symptom Inventory. Results: Of the 570 248 post-9/11 veterans in this sample, 0.45% had a diagnosis of vestibular dysfunction and 2.57% had nonspecific dizziness. Those with either condition were more likely to have evidence of TBI (57.11% vs 28.51%) and reported more disruption from neurobehavioral symptoms. Blast and nonblast injuries were associated with greater symptom disruption, particularly in combination. Conclusions: There was a consistent, significant association between TBI and vestibular dysfunction or nonspecific dizziness, after controlling for sociodemographic factors, injury mechanism, and comorbid conditions. Given that most deployed post-9/11 veterans report blast and/or nonblast injuries, the need for prompt identification and management of these conditions and symptoms is clear.